Озерные страсти: роман / Татьяна Алюшина - Алюшина Татьяна Александровна (Экcмо, 2021)
Экземпляры: ЦБ (20220627) / Инвентарный номер: 55169 / Цена: 323.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 59 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44